Foreword; News and Announcements - Peter J. Russell (Fungal Genetics Reports, 1997)
The 44th edition of the Fungal Genetics Newsletter contains articles and notes on a wide variety of topics. As usual, the aspergillus and neurospora bibliographies are included, as are a brief list of strains added to the FGSC collection since the publication of the most recent catalog in 1996 and the most recent FGSC mailing list.